Entre transición política y neoliberalismo: el Barzón mexicano - Rea Rodríguez, Carlos Rafael (Universidad de Costa Rica, 2022)
The present work analyzes the state of collective action in Mexico in the context of the exhaustion of the popular-nationalist model and the instalation of unbridled neo-liberalism. It places special emphasis on the case of a debtors movement, known as El Barzón, which began in 1993. This mobilization represents a form of organized response from the mid-level productive and service sectors of the country, in the face of confiscatory policies enacted against them by the banking and finance sectors, with the complicity of the Mexican state.